(untitled) (The Batuk, 2025)
This study investigates the consumer purchase intentions towards electric two-wheelers in Kathmandu Valley. The research examines the roles of environmental concerns, perceived economic benefits, social influence, and charging infrastructure. Data were collected from 400 respondents through a structured questionnaire survey, and hierarchical multiple regression was used for the causal analysis. Results indicate that environmental concerns are a strong motivator for adopting e-bikes, highlighting the potential for leveraging environmental benefits in marketing strategies. Perceived economic benefits also play a crucial role, suggesting that financial incentives could enhance e-bike appeal. Social influence emerged as a powerful factor, indicating that endorsements from peers and social networks can significantly shape purchase intentions. Despite these positive influences, high initial costs and inadequate charging infrastructure remain significant barriers. The study suggests that addressing these barriers through targeted interventions such as subsidies, improved charging infrastructure, and public awareness campaigns, is essential for promoting e-bike adoption. The findings provide valuable insights for policymakers and industry stakeholders to design strategies that support the transition to sustainable transportation, contributing to a cleaner environment and improved public health in Kathmandu Valley.